Safflower, Carthamus tinctorius L. - Dajue, L.; Mündel, H.; International Plant Genetic Resources Institute (1996)
Safflower is one of humanity's oldest crops but it generally has been grown on small plots for domestic use and remains a minor crop with a world seed production of about 800 000 t per year. This monograph overviews existing knowledge of the genus with emphasis on genetic resources. Chapters cover the following topics: taxonomy, nomenclature, centres of diversity, botany, production, genetics, uses, breeding, research priorities and constraints, collecting, and evaluation. Information on institutions holding safflower collections and undertaking research is also included. (Abstract © CAB ABSTRACTS, CAB International)